TRANSFORMASI DIGITAL: FINANCIAL TECHNOLOGY SEBAGAI PENDUKUNG UTAMA KINERJA UMKM DI TABANAN - Prawitasari, Putu Putri; Dinatha Putra, Putu Esa (LPPM Universitas Bina Bangsa, 2025)
This study aims to examine the influence of financial literacy, financial inclusion, financial technology on the performance of MSMEs. The study population included 47,957 MSME actors in Tabanan Regency, with a sample of 100 respondents, selected using the purposive sampling method. The data used are primary data. Data analysis was carried out using SPSS version 30 software with the F test method, t test, determination coefficient test, multiple linear regression analysis, and classical assumption test. The empirical results of the study indicate that financial literacy, financial inclusion, and financial technology have a positive influence on the performance of MSMEs. Overall, the performance of MSMEs is proven to be significantly influenced by the three independent variables.